Assessment of farming systems and cover configuration options that enhance natural regulation of herbivorous arthropod abundance in maize-fields - Otieno, Nickson Erick (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhDConsEcol)--Stellenbosch University, 2018.